Expected quality of medical services in patients' opinion - Misztal-Okońska, Patrycja Agnieszka; Krawczyk, Wojciech (Journal of Education, Health and Sport, 2019)
Medical services are unique type of industry in which measurement, evaluation and improvement of quality is not evident. This is due to the fact that the final results, even fully correct and consistent with the current medical knowledge of the treatment process, are not always predictable. In the medical profession, the quality of services provided is largely based on the subjective perceptions of the patients, that is why the field requires a different approach than other services. Objective. The aim of the study was to elitic and hierarchize elements that are the most important and most displeasing for patients in the process of using medical services as those factors determine the perceived level of medical services' quality. Material and method. The research method used in the study was a diagnostic survey, the technique was author's questionnaire. The study was conducted from January to May 2016. During this period 185 surveys were completed for statistical analysis. Surveys were filled in by respondents who declared active use of services provided by Polish public health care institutions. Results and conclusions. Regardless of the age and gender of the respondents, responses were very similar and clearly indicated that the most important element that determines the assessment of services is competence of the staff (education, knowledge, experience but also respect for patients) and availability and waiting times. In turn, the most displeasing elements are: long waiting times for health services, long queues, difficulties with availability of health services, hasty medical visits (short, superficial visit without thourough medical interview). Results of the study show, that patients' expectations are reasonable and possible to meet by health care institutions.